Predictive values of senior school cCertificate examinations, University Matriculation Examination and socio-personal factors on academic performance of university freshmen in South West, Nigeria (2011)
This study, examined relationship among freshmen were selected at random (1423 West African Senior School Certificate males and 1095 females). Secondary data (WASSC), Setor School Certificate were collected from the selected (SSC). University Matriculation Examination (UME) scores, age, sex and academic self-efficacy of academic performance of university freshmen in southwest Nigeria. The study adopted a descriptive survey design of ex-post-facto type. The five federal universities in the southwest were selected using purposive sampling and 2518 university universities' records office and admission office. The Academic Self-confidence Scale (a -0.86) was used as a measure of academic self-efficacy while personal data form Was used 10 collect demographic information. Seven research questions were answered in the study. Correlenion and Multiple Regression were used as tools of analysis. The six variables (WASSC, SSC, UME scores, age, sex and academic self-efficacy) when combined, accounted for 54.6% of the total variance in the academic performance. There was also significant contribution of the independent variables (age, sex, academic self-efficacy, SSC, WASSC and UME scores) on academic performance of the participants [F(5.2512) 26.13 p 0.05]. Also, the WASSC made the most significant relative contribution to the prediction of academic performance (B 0.349; 1= 8.134; p< 0.05); followed by SSC (B= 0.300, t 6.125, p 0.05); academic 0.144, t 2.760, self-efficacy (B 0.153, 1-3.812, p 0.05) and then, age (B p<0.05). However, sex and UME scores were not potent predictors of academic performance of University freshmen. The six independent variables (WASSC, SSC, UME scores, age, sex and academic self-efficacy) considered in this study were potent factors to academic performance of university freshmen. Based on these findings, WASSC and SSC could be regarded as adequate entry qualifications into the university. Counselling intervention programme aims at enhancing academic self-efficacy of freshmen should be mounted during orientation programmes in the universities